(untitled) (Vietnam Journal of Community Medicine, 2026)
Purpose: To evaluate the anatomical and functional outcomes of sutured punctoplasty in the treatment of acquired punctal stenosis. Methods: A prospective interventional study without a control group included 42 eyes with punctal stenosis treated by sutured punctoplasty at the National Eye Hospital from April 2021 to October 2022. Epiphora severity was assessed using the Munk score, punctal stenosis was graded according to the Kashkouli grading system, and punctal diameter was measured by anterior segment optical coherence tomography (OCT). Outcomes were evaluated preoperatively and at 6 months postoperatively. Results: The mean patient age was 48 ± 3 years and 82% were female. The mean duration of epiphora was 26.5 ± 11.3 months. At 6 months postoperatively, the functional success rate was 90.9%, with complete success achieved in 71.4% and partial success in 19.5% of cases. The anatomical success rate was 92.9%. Mean punctal diameter increased significantly from 158.8 ± 49.8 µm to 346.6 ± 129.9 µm (p<0.05). Postoperative complications were minimal and transient. Conclusion: Sutured punctoplasty is a simple, safe, and effective surgical technique for management of acquired punctal stenosis, providing high anatomical and functional success rates with minimal complications.